The impacts of climate change on UK energy demand. Issue 3 (1st August 2015) - Roeder, Mirjam; Hill, Frances; Mander, Sarah; Conor, Walsh; Kuriakose, Jaise; Glynn, Steven; Calverley, Daniel; Wood, Frances Ruth
Abstract : The impacts of climate change on the energy system are diverse; this article focuses on the potential effects on UK energy demand and the ramifications for national infrastructure building on the findings of the UK's 2012 Climate Change Risk Assessment. It reviews the available literature, where it exists, on the relationships among current energy demand, weather and climate change, and the implications for these relationships due to mitigation plans and potential adaptation responses. The review highlights the mechanisms by which future climate change, in particular changes in mean and extreme temperature, could affect the annual amount of UK energy demand and the seasonal, daily and spatial variation of the impacts. Published literature quantifying the effects of climate change on UK energy demand is limited; thus, where evidence is not available, information on the current relationship between weather and demand is combined with expert judgement to highlight potential demand responses to a changing climate without quantification. The impacts identified could have significant implications for the long-term planning of energy infrastructure and system operation and building design, depending on their magnitude, highlighting the need for further research in this area.